P144 Clock gene expression levels inversely correlate with disease activity in ulcerative colitis and Crohn's disease. (27th May 2021) - Weintraub, Y; Cohen, S; Chapnik, N; Anafy, A; Yerushalmy-Feler, A; Ben-Tov, A; Dotan, I; Riva, T; Froy, O
Abstract: Background: Pathophysiological mechanisms active in inflammatory bowel disease (IBD), such as mucosal barrier repair, innate and adaptive immune responses, intestinal motility and gut microbiome, all exhibit diurnal variations. Chronic disruption of the molecular clock augment inflammatory response. We have shown that newly diagnosed, naïve to treatment, young IBD patients showed reduced clock gene expression in both inflamed and non-inflamed intestinal tissues and in peripheral White Blood Cells (WBC). This reduction correlated with disease activity. Our aim in this study was to determine whether certain clock genes correlate with disease activity scores or inflammatory markers in Crohn's disease (CD) vs. ulcerative colitis (UC). Methods: 17 patients with CD and 13 with UC, 8–22 years old, were recruited. Patients were evaluated upon diagnosis and during medical treatment. Disease activity scores, C-reactive protein (CRP) and fecal calprotectin (Fcal) levels were measured and WBC were analysed for clock gene ( CLOCK, BMAL1, CRY1, CRY2, PER1 and PER2 ) expression. Clock gene expression levels were correlated to disease activity scores (clinically active vs. remission), CRP levels (<5 mg/l vs. >5 mg/l) and Fcal levels (< 250 μg/mg vs. >250 μg/mg) in CD (21 samples) and UC (20 samples). Results: In UC, BMAL (p<0.008), CLOCK (p<0.02), CRY1 (p<0.002), CRY2 (p<0.0009), PER1 (p<0.003) and PER2 (p<0.003) showed decreased expression when Fcal levels were > 250 μg/mg. When compared with the clinical status and CRP levels, only BMAL1 showed reduced expression (p<0.003 and p<0.001, respectively). In CD, clinical status correlated with clock gene expression: CLOCK (p<0.035), PER1 (p<0.001) and CRY1 (p<0.028) were reduced in active disease. CRP and Fcal did not correlate with clock gene expression. Conclusion: Altered levels of certain clock genes were demonstrated in young CD and UC patients in exacerbation vs. remission. In UC, Fcal levels inversely correlated with all major circadian genes and partially with clinical status and CRP levels. In CD patients clock gene expression inversely correlated with clinical status.